2010
DOI: 10.1007/s10943-010-9404-1
|View full text |Cite
|
Sign up to set email alerts
|

Centering Prayer as an Alternative to Mindfulness-Based Cognitive Therapy for Depression Relapse Prevention

Abstract: In the last two decades, mindfulness has made a significant impact on Western secular psychology, as evidenced by several new treatment approaches that utilize mindfulness practices to ameliorate mental illness. Based on Buddhist teachings, mindfulness offers individuals the ability to, among other things, decenter from their thoughts and live in the present moment. As an example, mindfulness-based cognitive therapy (MBCT) teaches decentering and mindfulness techniques to adults in an eight-session group thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 11 publications
0
31
0
2
Order By: Relevance
“…This finding is relatively unexpected given that mantra meditation and mindfulness meditation derive from Hinduist and/or Buddhist tradition33 and thus originate from Asia. However, this might at least partly be explained by the fact that spiritual meditation was the category practiced most often, and this category included centering prayer which originally derives from Christian tradition34. Prior analyzes of the 2012 NHIS have shown that while Asians in the US were also less likely to practice yoga as compared to non-Hispanic Whites11, they were more likely to practice Tai Chi or Qigong12.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is relatively unexpected given that mantra meditation and mindfulness meditation derive from Hinduist and/or Buddhist tradition33 and thus originate from Asia. However, this might at least partly be explained by the fact that spiritual meditation was the category practiced most often, and this category included centering prayer which originally derives from Christian tradition34. Prior analyzes of the 2012 NHIS have shown that while Asians in the US were also less likely to practice yoga as compared to non-Hispanic Whites11, they were more likely to practice Tai Chi or Qigong12.…”
Section: Discussionmentioning
confidence: 99%
“…The associations of yoga, prayer and multiple practices might be seen as simply due to the meditative components contained in each (Knabb, 2012). Unfortunately, this attractive and parsimonious hypothesis cannot be asserted unequivocally.…”
Section: Discussionmentioning
confidence: 99%
“…Knabb (2012) notes that "mindfulness" used in psychotherapy (such as mindfulness-based cognitive therapy) is based on Buddhist teachings. He 704 D.D.…”
Section: Religious Psychotherapymentioning
confidence: 99%